Impact of Cancer History on Outcomes Among Hospitalized Patients with COVID‐19. (12th May 2021) - Klein, Isaac A.; Rosenberg, Shoshana M.; Reynolds, Kerry L.; Zubiri, Leyre; Rosovsky, Rachel; Piper‐Vallillo, Andrew J.; Gao, Xin; Boland, Genevieve; Bardia, Aditya; Gaither, Rachel; Freeman, Hannah; Kirkner, Gregory J.; et al.
Abstract: Background: Early reports suggested increased mortality from COVID‐19 in patients with cancer but lacked rigorous comparisons to patients without cancer. We investigated whether a current cancer diagnosis or cancer history is an independent risk factor for death in hospitalized patients with COVID‐19. Patients and Methods: We identified patients with a history of cancer admitted to two large hospitals between March 13, 2020, and May 10, 2020, with laboratory‐confirmed COVID‐19 and matched them 1:2 to patients without a history of cancer. Results: Men made up 56.2% of the population, with a median age of 69 years (range, 30–96). The median time since cancer diagnosis was 35.6 months (range, 0.39–435); 80% had a solid tumor, and 20% had a hematologic malignancy. Among patients with cancer, 27.8% died or entered hospice versus 25.6% among patients without cancer. In multivariable analyses, the odds of death/hospice were similar (odds ratio [OR], 1.09; 95% confidence interval [CI], 0.65–1.82). The odds of intubation (OR, 0.46; 95% CI, 0.28–0.78), shock (OR, 0.54; 95% CI, 0.32–0.91), and intensive care unit admission (OR, 0.51; 95% CI, 0.32–0.81) were lower for patients with a history of cancer versus controls. Patients with active cancer or who had received cancer‐directed therapy in the past 6 months had similar odds of death/hospice compared with cancer survivors (univariable OR, 1.31; 95% CI, 0.66–2.60; multivariable OR, 1.47; 95% CI, 0.69–3.16). Conclusion: Patients with a history of cancer hospitalized for COVID‐19 had similar mortality to matched hospitalized patients with COVID‐19 without cancer, and a lower risk of complications. In this population, patients with active cancer or recent cancer treatment had a similar risk for adverse outcomes compared with survivors of cancer. Implications for Practice: This study investigated whether a current cancer diagnosis or cancer history is an independent risk factor for death or hospice admission in hospitalized patients with COVID‐19. Active cancer, systemic cancer therapy, and a cancer history are not independent risk factors for death from COVID‐19 among hospitalized patients, and hospitalized patients without cancer are more likely to have severe COVID‐19. These findings provide reassurance to survivors of cancer and patients with cancer as to their relative risk of severe COVID‐19, may encourage oncologists to provide standard anticancer therapy in patients at risk of COVID‐19, and guide triage in future waves of infection. Abstract : This article focuses on whether a current cancer diagnosis or cancer history is an independent risk factor for death or hospice admission in hospitalized patients with COVID‐19.